2021
DOI: 10.47583/ijpsrr.2021.v68i01.026
|View full text |Cite
|
Sign up to set email alerts
|

Computational Repurposing Model of Curcumin as a Drug

Abstract: Viral diseases continue to be a public threat on a global scale day by day and the world is in a continuing battle with the novel deadly viral Diseases and with no prompt medicines accessible the scourge brought about by the disease is expanding step by step. The ongoing need to develop new antiviral drugs with fewer side-effects and that are effective against viral pathogens has spurred the research community to invest in various drug discovery strategies, one of which is drug repurposing the methods of findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The whole IAV genome codes for different proteins including NA (neuraminidase), RNA polymerases (PB1, PB2, and PA), HA, M1 (matrix proteins), M2 (ion channel), and NP (nucleoprotein) (Hutchinson, 2018). In silico studies targeting NA, PB2, HA, M1, and M2, as well as different signaling pathways (AKT1, TP53, MAPK1, and RELA) illustrated that curcumin and its different derivatives act as acceptable inhibitors of these proteins and pathways (Jayasree et al, 2014; Kim, Choi, Kim, Kang, & Kim, 2021b; Richart et al, 2018; Roy et al, 2021; Satpathy et al, 2012; Singh & Misra, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The whole IAV genome codes for different proteins including NA (neuraminidase), RNA polymerases (PB1, PB2, and PA), HA, M1 (matrix proteins), M2 (ion channel), and NP (nucleoprotein) (Hutchinson, 2018). In silico studies targeting NA, PB2, HA, M1, and M2, as well as different signaling pathways (AKT1, TP53, MAPK1, and RELA) illustrated that curcumin and its different derivatives act as acceptable inhibitors of these proteins and pathways (Jayasree et al, 2014; Kim, Choi, Kim, Kang, & Kim, 2021b; Richart et al, 2018; Roy et al, 2021; Satpathy et al, 2012; Singh & Misra, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Establishment of molecular techniques for assessment of anti-HTNV compounds revealed that curcumin could decrease viral RNA levels in different organs of mouse animal model (Wei et al, 2013). One in silico approach also noted acceptable docking results for curcumin against HTNV envelope glycoprotein (Roy et al, 2021).…”
Section: Hantaan Virusmentioning
confidence: 99%